2022
DOI: 10.1145/3461697
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Approach for Rumor Detection of Arabic Tweets Using eXtreme Gradient Boosting Method

Abstract: Twitter is currently one of the most popular microblogging platforms allowing people to post short messages, news, thoughts, and so on. The Twitter user community is growing very fast. It has an average of 328 million active accounts today, making it one of the most common media for getting information during any influential or important event. Because it is freely used by the public, some credibility checking is required, especially when it comes to events of high importance. Automatic rumor detection in Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…• Arabic ChatGPT Tweets Classification: This paper's [82]discussion will focus on the methodology and performance of the hybrid transformer-based model used for sentiment classification of Arabic tweets about Chat-GPT. Numerical values provided in the abstract include a 96.02% accuracy rate for the hybrid model, 100% precision on negative tweets, and 99% recall for neutral tweets, which are significant metrics indicating the model's performance.…”
Section: Computer Science and Itmentioning
confidence: 99%
“…• Arabic ChatGPT Tweets Classification: This paper's [82]discussion will focus on the methodology and performance of the hybrid transformer-based model used for sentiment classification of Arabic tweets about Chat-GPT. Numerical values provided in the abstract include a 96.02% accuracy rate for the hybrid model, 100% precision on negative tweets, and 99% recall for neutral tweets, which are significant metrics indicating the model's performance.…”
Section: Computer Science and Itmentioning
confidence: 99%
“…Regardless, it solely focuses on detection and does not consider essential postings or influential spreaders, leading to real-time challenges in monitoring and controlling events in (Ren et al, 2022). Some classification methods are categorized as feature-pivot based and can detect irrelevant or unconfirmed tweets by using such as eXtreme Gradient Boosting (XGBoost) (Gumaei et al, 2022), Multi-Layer Perceptron (MLP) (Mredula et al, 2022), and Naive Bayes (NB) (Sufi & Khalil, 2022). Compared to others, XGBoost and MLP outperform other approaches, particularly for opinion identification in response to a specific event (Bravo-Marquez et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors in [28] extracted two types of features from the text, content-based and topic-based, in addition to extracting user-based features. The XGBoost algorithm was used, and the results indicated that the proposed model achieved an accuracy of 97%.…”
Section: A Rumor Detection Using Unimodal Approachesmentioning
confidence: 99%